Avaliação do extrato aquoso da casca de Picramnia excelsa (PICRAMNIACEAE) como hipoglicemiante e no tratamento da obesidade - Nascimento, Eunildo Macedo do (2019)
Recognized as a disease by the World Health Organization, obesity is considered as a health problem that affects all age groups. Excessive consumption of fat and glucose can lead to obesity, which in turn can lead to several chronic diseases, such as diabetes mellitus, a metabolism disorder characterized by hyperglycemia. Although there are medications to treat obesity, most of them cause many side effects. In this context, herbal medicine has been the object of interest of researchers because it has great potential as an alternative to obesity treatment. Picramnia excelsa has a popular indication for the treatment of obesity and diabetes, however, there are no studies in the literature to prove its effectiveness. Given the above, this study aimed to: make a survey of herbal medicine in the treatment of obesity regarding its effectiveness, action and safety; and to evaluate if Picramnia excelsa favors weight and glycemia reduction in male Wistar rats. Male non-obese albino Wistar rats were fed with hypercaloric food for 24 weeks to induce obesity and diabetes mellitus and were weighed every 7 days. After the final period of obesity and diabetes induction, the animals were divided into three groups, CN (negative control that received no water), group 10% (group that received 10% aqueous extract at a dose of 21 mg / kg) and group 20% (group that received 10% aqueous extract at a dose of 29 mg / kg). Each group consisted of 12 animals and received the extract via esophageal gavage for 30 days. Animals were weighed every 3 days during treatment. Also, they were submitted to oral glucose tolerance test (TTGo) before the onset of obesity induction, before the treatment, and after 30 days of treatment with the aqueous extract. The data obtained were analyzed by ANOVA statistical tests followed by Fisher's LSD posHoc, or Kruskal-Wallis followed by the Wilcoxon Matches Pairs test. The obesity and diabetes induction process occurred as expected, and after 24 weeks of induction, the animals were obese and insulin resistant. The CN group rats had an average increase of 44.53% in relation to the initial weight during obesity induction period. the treatment. Corroborating the decrease in fattening rate, the 10% group presented a significantly lower triglyceride level than the CN and 20% groups. Although all groups showed glucose intolerance at the end of the experiment (165.37 mg / dL, 164 mg / dL and 144.62 mg / dL for control groups, 10% and 20%, respectively), the 20% group presented the greatest reduction in glucose level after 120 min, p <0.10. Considering that this study was a preliminary test to evaluate the potential of P. excelsa, the obtained results are promising in the obesity control. However, research should be developed using a longer treatment time to determine the best aqueous extract concentration for treatment.